The endangered species Aristelliger georgeensis (Squamata: Sphaerodactylidae) in Roncador Cay, Colombian Caribbean (2015)
ABSTRACT : Aristelliger georgeensis, previously known to occur in the Yucatan peninsula (Mexico), the coasts and islands from Belize and Honduras, and the oceanic islands of Colombia in the Caribbean (San Andres, Providence and Saint Catalina) was registered for the first time in Roncador Cay, a flat and small island of coralline origin, located in the southwest of the Caribbean. Being considered as an endangered species at the national level, the new locality for this gecko constitutes an opportunity for its conservation. Some topics regarding the possible origins of this new population are discussed. This new locality represents the eastern most documented record of this species so far.